PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN FASILITAS K3 TERHADAP BUDAYA KESELAMATAN (SAFETY CULTURE) DI SEKOLAH MENENGAH PERTAMA PADA ERA PASCA PANDEMI - Wahyuni, Riscky Fitri; Aini, Nur (STKIP Pesisir Selatan, 2026)
This research is driven by the urgent need to strengthen safety culture within educational institutions as a response to the complex challenges of the post-pandemic era. The study aims to examine the influence of principal safety leadership and school occupational health and safety (OHS) facilities on students’ safety culture. A quantitative explanatory design was employed, involving 100 students selected through simple random sampling from a population of 455 students at a junior secondary school in Sungai Penuh City, Indonesia. Data were collected using validated Likert-scale questionnaires, systematic observation, and documentation, then analyzed using multiple linear regression. The findings reveal that principal safety leadership has a positive and significant effect on students’ safety culture (β = 0.311, p = 0.006). School OHS facilities also demonstrate a positive and significant influence (β = 0.389, p = 0.002), indicating a stronger contribution than leadership variables. Simultaneously, both predictors significantly affect students’ safety culture (F = 102.48, p < 0.001), with an explanatory power of 68.1% (R2 = 0.681). These results suggest that adaptive leadership practices combined with adequate safety facilities are critical determinants in fostering a sustainable and resilient school safety culture.